Efficacy of a Preference-Based Decision Tool on Treatment Decisions for a First-Time Anterior Shoulder Dislocation: A Randomized Controlled Trial of At-Risk Patients. (April 2019) - Hutyra, Carolyn A.; Smiley, Stephen; Taylor, Dean C.; Orlando, Lori A.; Mather, Richard C.
Background. First-time anterior shoulder dislocations (FTASD) provide an opportunity to examine the value of integrating stated-preference data with decision modeling to differentiate between patients whose preferred management strategy involves operative or nonoperative treatment. The objective of this study was to evaluate the efficacy of a FTASD decision tool intervention with individual preference measurement compared with a text-based control in a randomized controlled trial.Methods. Two hundred respondents between 18 and 35 years of age at risk for experiencing an FTASD were enrolled from the orthopedic clinics and randomized to receive either an interactive decision tool intervention capable of eliciting patient preferences for treatment of an FTASD or a text-based control on shoulder dislocations and treatments. The primary outcome was preference for operative or nonoperative treatment choice. Secondary outcomes included the decisional conflict scale (DCS), stage of decision making, patient activation and engagement, awareness of preference sensitive decisions, knowledge retention, and instrument acceptability.Results. One hundred respondents were randomized to the intervention and 100 to the control. A total of 154 men and 46 women with an average age of 23.6 years completed the survey. Participants in the intervention group made treatment decisions that aligned more closely with evidence-based recommendations than those in the control group ( P = 0.016). Secondary outcomes showed no difference between intervention and control, excluding several DCS subscales.Discussion. An interactive, preference-based decision tool for treatment of FTASD affects patient decision making by guiding respondents toward treatment decisions that align more closely with evidence-based recommendations in the absence of a consultation with an orthopedic provider compared with a standard-of-care control tool. Additional study is needed to evaluate the long-term effects of this tool on treatment outcomes, patient adherence, and satisfaction.LEVEL OF EVIDENCE: 2